Recruitment for a multi‐site randomized controlled trial of aerobic exercise for older adults with amnestic mild cognitive impairment: The EXERT trial: Prevention (nonpharmacological) / Exercise. (7th December 2020) - LaCroix, Andrea Z; van Dyck, Christopher H; Okonkwo, Ozioma C; Tam, Steven P; Fairchild, Jennifer Kaci; Li, Clara; Welsh‐Bohmer, Kathleen A; Shadyab, Aladdin H; Matthews, Genevieve; Bennett, Daniel; Shadyab, Alexandre; Schafer, Kimberly A; et al.
Abstract: Background: EXERT is a large multi‐site randomized controlled trial testing the effects of aerobic exercise vs. stretching (control) on cognition and biomarkers of brain health in sedentary adults with MCI. Here, we describe challenges and successes of strategies used to recruit the EXERT cohort. Method: EXERT recruited sedentary adults 65‐89 years old who were willing to exercise 4 days/week at the YMCA with trainer supervision for 12 months, and unsupervised for an additional 6 months. The trial is conducted at 14 clinical sites that include 30 corresponding YMCAs. The ADCS serves as the Coordinating Center, and intervention oversight is provided by Wake Forest School of Medicine in partnership with the YMCA. Result: EXERT recruitment occurred over 43 months and several strategies were deployed to address recruitment challenges. The most notable challenge was that EXERT aimed to recruit adults with a cognitive impairment that is mentally/physically taxing given the expectations of an intensive exercise intervention study. For these individuals, transportation to the YMCA was also often a barrier to participation. Early recruitment methods relied on memory clinic patient rosters and electronic health records, which yielded only a few enrollments. Use of other common strategies (e.g., newspaper advertising) was only minimally successful in identifying candidates. Recruitment gained momentum only after geotargeted mailings of pictorial postcards and brochures were initiated. After the first mailing at 3 sites, the rate of in‐person screenings increased by more than 100% (Figure 1). In total, 500, 000 geotargeted mailings across all sites were sent from which more than 50% of all randomized participants were recruited. Recruitment also benefited from high‐profile media coverage (Maria Shriver video, NPR) in 2018 and 2019. Early in 2019, the ADCS established centralized telephone prescreening to reduce burden on site staff. A total of 692 mailing responders were prescreened by the ADCS, of whom 228 were referred to sites. As of January 2020, 984 study candidates completed in‐person screening and 278 participants were enrolled into EXERT. Conclusion: Age and geotargeted mass mailings combined with centralized telephone prescreening and national media campaigns proved to be effective strategies for enrolling people with MCI in a long‐term exercise trial.